Assessment of microbiological growth on surgical face mask - Bin Amir, Adam; Aini Dahalan, Farrah; Anjarwati, Lutfiah; R. Kurniawan, Wildan (Environmental and Toxicology Management, 2022)
Wearing surgical face masks for a long time has a number of physiologic and psychological consequences, as well as the potential to reduce work efficiency. Physical side effects of long-term usage of surgical masks include headaches, trouble breathing, acne, skin breakdown, rashes, and reduced memory. It also obstructs eyesight, communication, and thermal balance. The objective of this research was to investigate the effects of bacteria growth and type of bacteria morphology present on the face mask. Serial dilutions were used to calculate the concentration of microorganisms. As it would usually be impossible to actually count the number of microorganisms in a sample, the sample was diluted and plated to get a reasonable number of colonies to count. Since the dilution factor was known, the number of microorganisms Log CFU per mL was calculated. The CFU count results clarify the growth curve pattern of bacteria formed on agar plate surfaces and revealed some details of bacterial life after their adhesion onto surfaces in the presence of agar. This growth curve exhibited distinct phases: the lag phases, the exponential (log) phases, the stagnant phases and the dead phases. Gram staining and hanging drop method was used to identify the gram positive, gram negative and the bacteria morphology. This study provides insightful on the investigation of bacteria present on surgical face masks which is little available in literature.